The Brokenwood mysteries. Series 7 [videorecording (DVD)] - Rea, Neill, 1971-; Sutherland, Fern; Rawiri, Jarod (Acorn Media, 2021)
In the sleepy town of Brokenwood, New Zealand, the affable residents may seem harmless, but killers, blackmailers, and thieves lurk in every picturesque corner. To quell the community's alarming murder rate, Detective Mike Shepherd uses an unconventional style that contrasts with the methodical approach of his partner, Detective Kristin Sims, and the eager assistance of DC Sam Breen.